Special berries to the market - a development project cutting the local agro-food chain - Korpelainen, Ville; Hoppula, Kalle; Théroux Rancourt, Guillaume; Ervasti, Hanna; Mannila, Mari; Virtanen, Vesa; Heikkilä, Raimo; Pirinen, Heli (se, 2006)
v ok